HIV Modulates Osteoblast Differentiation via Upregulation of RANKL and Vitronectin - Rosa Nicole Freiberger; Cynthia Alicia Marcela López; María Belén Palma; Cintia Cevallos; Franco Agustin Sviercz; Patricio Jarmoluk; Marcela Nilda García; Jorge Quarleri; M. Victoria Delpino (Pathogens)
Bone loss is a prevalent characteristic among people with HIV (PWH). We focused on mesenchymal stem cells (MSCs) and osteoblasts, examining their susceptibility to different HIV strains (R5- and X4-tropic) and the subsequent effects on bone tissue homeostasis. Our findings suggest that MSCs and osteoblasts are susceptible to R5- and X4-tropic HIV but do not support productive HIV replication. HIV exposure during the osteoblast differentiation process revealed that the virus could not alter mineral and organic matrix deposition. However, the reduction in runt-related transcription factor 2 (RUNX2) transcription, the increase in the transcription of nuclear receptor activator ligand kappa B (RANKL), and the augmentation of vitronectin deposition strongly suggested that X4- and R5-HIV could affect bone homeostasis. This study highlights the HIV ability to alter MSCs’ differentiation into osteoblasts, critical for maintaining bone and adipose tissue homeostasis and function.